ANALYSIS OF PERCEPTUAL PHENOMENON ON MOVEMENT OBSERVATION: INTERPRETATION OF MORPHOLOGICAL VIEWPOINT AS "DOPPELTER GESTALTKREIS" - Matsuyama Naoki (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
The purpose of this study is to clarify the Morphorogical Viewpoint on Movement Observation from phenomenological standpoint. Generally, Movement Observation is interpreted by two viewpoints. First is the Morphological Viewpoint (MOV) which is based on phenomenological morphology. Second is the Mechanistic Viewpoint, which is based on physics. The former corresponds to the core ability of coaches and physical teachers (Meinel, 1981) because the MOV is focused on the generation of movement. However some coaches and physical teachers cannot properly interpret the MOV (Meinel, 1981; Muraki, 1993). In some previous studies, the MOV has been interpreted from applying Gestaltkreis (Weizsäcker, 1940) which is a phenomenological hermeneutic figure for perceiving sound of "Melody of Movement" (Buytendijk, 1958). However, MOV's Perceptual Phenomenon has not been directly clarified as hermeneutic figure. Because of this, this study deductively analyzes Perceptual Phenomenon of MOV from the relevance of consciousness and perception. On the base of their relevance, this study furthermore conceptualizes "Doppelter Gestaltkreis" which is a hermeneutic figure for directive interpretation of MOV's Perceptual Phenomenon. This study further discusses the utility of Doppelter Gestaltkreis for enlarging the observation horizon of coaches and physical teachers.